Zirconium-silicon-based glass ceramic with ultrahigh toughness and bending strength and preparation method of zirconium-silicon-based glass ceramic
By alloying different elements and sintering nano-scale amorphous powders, zirconium silicon-based glass ceramics with high bending strength and fracture toughness were prepared, which solved the problem of insufficient toughness of existing glass ceramic materials and achieved excellent mechanical properties.
Patent Information
- Application Number
- CN202411385243.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
The lack of toughness and flexural strength of existing glass ceramic materials limits their application in high load areas and is difficult to meet the needs of modern dental technology to improve material performance.
Using ZrO2-SiO2 glass ceramics to alloy metal oxides with different valence states and cationic radii, a new zirconium silicon-based nanocrystalline glass ceramic system was developed, and the doped cationic high-purity nano-scale amorphous powder was prepared by precipitation method, and the Sintered nano-scale amorphous powder to obtain zirconium silicon-based glass ceramics, ZrO2 spherical nanograins are introduced into the amorphous SiO2 matrix, and the doped elements are partially aggregated at the interface layer.
The material has a zirconia formula of up to 25-70% with an average grain size of less than 100nm. The material's bending strength exceeds 500MPa, the fracture toughness exceeds 4MPa, and the maximum can exceed 12MPa, which significantly improves mechanical properties.
Smart Images

Figure CN119241079A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass ceramics, and in particular to zirconium-silicon-based glass ceramics with ultra-high toughness and bending strength and a preparation method thereof. Background Art
[0002] Dental glass ceramics are an important type of oral restorative materials and are widely used in the production of restorations such as crowns, bridges, inlays, veneers, etc. Glass ceramic materials were first developed and applied to dentistry in the 1960s. After years of research and technological development, they have become a mainstream restorative material on par with metal and resin-based materials. The main features of glass ceramics are their unique aesthetic effects and excellent biocompatibility. Its translucency and optical properties similar to those of natural teeth make the appearance of the restoration in the mouth very close to that of natural teeth. This feature makes glass ceramics particularly suitable for the restoration of the aesthetic area of the anterior teeth. In addition, the color of the glass ceramic material can be finely adjusted according to the color of the patient's teeth to achieve the ideal aesthetic effect.
[0003] In addition to its aesthetic properties, the chemical properties of glass ceramics also make it an excellent restorative material. Its main components often include silicon dioxide, aluminum oxide, potassium oxide, sodium oxide, etc., and it has good chemical compatibility with human tissue. This material does not cause immune reactions or allergies, has good biocompatibility, and its surface is smooth and not easy to accumulate dental plaque, which is conducive to the long-term maintenance of oral health.
[0004] In terms of mechanical properties, dental glass ceramics can achieve relatively high strength through different strengthening processes, such as crystal precipitation and heat treatment. Common types of glass ceramics include materials with different compositions such as feldspar, alumina, lithium disilicate, and phosphate crystals. Each glass ceramic type has different physical properties and can adapt to different restoration needs. For example, lithium disilicate glass ceramics are widely used for posterior tooth restorations that withstand high bite forces due to their high strength and toughness.
[0005] However, despite the many advantages of glass-ceramics, their brittleness still limits their application in high-load areas, and their low toughness limits the wider application of glass-ceramic materials. Enhancing the toughness of glass-ceramics remains a major challenge, even for all-ceramic materials, where planar slip is almost impossible due to their inherent properties. With the continuous improvement of material performance requirements, modern dental technology has also posed new challenges to glass-ceramics, including improving their mechanical properties without sacrificing aesthetic effects, as well as improving efficiency and reducing losses during processing.
[0006] At present, the strength of glass ceramics can be improved by the following methods: (1) Crystal precipitation strengthening: Introducing crystalline phases (such as lithium disilicate crystals or phosphate crystals) into the glass matrix, and promoting the precipitation of crystals in the matrix through heat treatment. These micron or nanometer crystals can prevent the propagation of cracks, thereby enhancing the crack resistance of the material. (2) Toughening mechanism: Common toughening mechanisms in research include crack blunting and crack deflection. When the crack propagates to the crystal or matrix interface, the crack path will be deflected or blocked, reducing the crack propagation rate, thereby improving the toughness of the material. (3) Particle or fiber reinforcement: By introducing other phases (such as zirconium oxide particles or fibers) into glass ceramics, the fracture toughness of the material can be effectively enhanced. These reinforcing phases can provide stress dispersion at stress concentration points, thereby reducing the formation and propagation of microcracks. However, the strengthening results of these mechanisms are limited, and the current glass ceramics are far from meeting clinical requirements. Therefore, new methods and mechanisms are needed. Summary of the invention
[0007] The purpose of the present invention is to provide a zirconium-silicon-based glass-ceramic with ultra-high toughness and bending strength and a preparation method thereof, so as to solve the problem of poor toughness of existing glass-ceramic materials.
[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0009] The present invention provides a zirconium-silicon-based glass ceramic with ultra-high toughness and flexural strength, wherein the zirconium-silicon-based glass ceramic comprises the following components in molar percentage:
[0010] X 1~15%, ZrO225~70%, SiO225~70%;
[0011] Here, X is a metal oxide having a valence of +1 to +5.
[0012] Preferably, in the above-mentioned zirconium-silicon-based glass-ceramics having ultra-high toughness and flexural strength, X is K2O, MgO, Al2O3, Y2O3, CeO2 or Ta2O5.
[0013] The present invention also provides a method for preparing zirconium-silicon-based glass ceramics with ultra-high toughness and flexural strength, comprising the following steps:
[0014] Mixing a precursor of X, a zirconium-based precursor, a silicon-based precursor and an alcohol solution to obtain a mixed solution;
[0015] adding an alkaline solution to the mixed solution for reaction, and aging the solution after the reaction is completed to obtain nanogel particles;
[0016] calcining the nanogel particles to obtain powder;
[0017] The powder is sintered to obtain zirconium-silicon-based glass ceramics.
[0018] Preferably, in the above-mentioned method for preparing zirconium-silicon-based glass-ceramics with ultra-high toughness and flexural strength, the precursor of X is potassium chloride, potassium nitrate, potassium isopropoxide, magnesium chloride, magnesium nitrate, aluminum chloride, aluminum nitrate, isopropoxide aluminum, yttrium chloride, yttrium nitrate, triisopropoxyyttrium, cerium chloride, cerium nitrate hexahydrate, tetraisopropoxycerium, tantalum nitrate, pentaisopropoxytantalum or tantalum chloride;
[0019] The zirconium-based precursor is zirconium n-propoxide, zirconium dichloride or zirconium nitrate;
[0020] The silicon-based precursor is tetraethyl orthosilicate, ethyl silicate, tetramethoxysilane or tetraisopropoxysilane;
[0021] The alcohol solution is propanol or anhydrous ethanol.
[0022] Preferably, in the above-mentioned method for preparing zirconium-silicon-based glass-ceramics with ultra-high toughness and flexural strength, the dosage ratio of the zirconium-based precursor to the alcohol solution is 0.5:1 to 1:10.
[0023] Preferably, in the above-mentioned method for preparing zirconium-silicon-based glass-ceramics with ultra-high toughness and flexural strength, the mixing temperature is 20-50° C., the mixing time is 0.5-2 h; and the mixing rotation speed is 500-1500 rpm.
[0024] Preferably, in the above-mentioned method for preparing zirconium-silicon-based glass ceramics with ultra-high toughness and flexural strength, the alkaline solution is an ammonia solution or a sodium hydroxide solution;
[0025] The concentration of the alkaline solution is 0.1-2 mol / L;
[0026] The volume ratio of the alcohol solution to the alkaline solution is 1 to 8:1.
[0027] Preferably, in the above-mentioned method for preparing zirconium-silicon-based glass-ceramics with ultra-high toughness and flexural strength, the aging temperature is 20 to 90° C., and the aging time is 0.5 to 72 hours.
[0028] Preferably, in the above-mentioned method for preparing zirconium-silicon-based glass-ceramics with ultra-high toughness and flexural strength, the calcination conditions are: the initial temperature is 20-30°C, the final temperature is 400-700°C, the rate of rising from the initial temperature to the final temperature is 0.5-5°C / min, and the time of keeping at the final temperature is 30-180min.
[0029] Preferably, in the above-mentioned method for preparing zirconium-silicon-based glass ceramics with ultra-high toughness and flexural strength, the sintering method is pressureless sintering, hot pressing sintering, hot isostatic pressing sintering or rapid sintering;
[0030] The rapid sintering is spark plasma sintering or rapid hot pressing sintering.
[0031] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0032] In the present invention, ZrO2-SiO2 glass ceramics are prepared by alloying with alloy elements (K + (138pm), Mg 2+ (89pm), Al 3+ (54pm), Ce 4+ (97pm) and Ta 5+ (74pm)) alloying to develop a new tough and damage-resistant zirconium-silicon-based nanocrystalline glass-ceramic system. High-purity nanoscale zirconium-silicon-based amorphous powders doped with cations (K2O, MgO, Al2O3, CeO2, Ta2O5) were prepared by precipitation method; zirconium-silicon-based glass-ceramics were obtained by sintering the nanoscale amorphous powders. This method introduces a new strategy: instead of weakening the nanointerfaces in glass-ceramics, the nanointerfaces are further strengthened by alloying different elements to strengthen the brittle inorganic materials. This prevents the formation of a single main crack and creates an intermediate stage between strengthening and weakening.
[0033] The present invention can realize a material formula containing up to 25-70% (molar ratio) of zirconium oxide. The average grain size of the sintered material is less than about 100nm, and the smallest can be less than 50nm. The obtained material shows excellent mechanical properties.
[0034] The zirconium-silicon-based glass-ceramic spherical single crystal ZrO2 spherical nano-grains prepared by the present invention are embedded in an amorphous SiO2 matrix, and the doping elements (K, Mg, Al, Ce, Ta) are concentrated in the interface layer, wherein the ZrO2 content exceeds 50% (volume ratio), and the bending strength of the material exceeds about 500MPa, and the highest exceeds 900MPa, and the fracture toughness exceeds about 4MPa, and can exceed 12MPa at most. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.
[0036] Figure 1The mechanical properties of zirconium-silicon-based glass ceramics and lithium silicate glass ceramics in Examples 1 to 5; wherein, (a) the toughness and flexural strength of zirconium-silicon-based glass ceramics in Examples 1 to 5; (b) the nanohardness and elastic modulus of zirconium-silicon-based glass ceramics in Examples 1 to 5; (c) the flexural strength and toughness of lithium silicate glass ceramics, the illustration in (c) is a comparison of the indentation marks of lithium silicate glass ceramics and zirconium-silicon-based glass ceramic 5MgO-65ZrO2-30SiO2 in Example 2 under an applied load of 1kgf; (d) the fracture of zirconium-silicon-based glass ceramic 5MgO-65ZrO2-30SiO2 in Example 2 Surface SEM images, the inset in (d) is a higher magnification SEM image of the fracture surface of 5MgO-65ZrO2-30SiO2; (e) Appearance of lithium silicate glass ceramics and zirconium-silicon-based glass ceramics 5MgO-65ZrO2-30SiO2 in Example 2 after a load of 30kgf is applied; (f) Representative indentation crack end SEM image of zirconium-silicon-based glass ceramics 5MgO-65ZrO2-30SiO2 in Example 2; (g) Representative indentation crack end SEM image of 5MgO-65ZrO2-30SiO2 after etching with hydrofluoric acid (HF);
[0037] Figure 2 The SEM images of the indentation marks of the lithium silicate glass ceramics and the zirconium-silicon-based glass ceramics in Examples 1 to 5 under loads of 1kgf, 5kgf and 10kgf, wherein the scales in the SEM images of the indentation marks of the lithium silicate glass ceramics under loads of 1kgf, 5kgf and 10kgf are 70μm, 100μm and 100μm, respectively; the scales in the SEM images of the indentation marks of the zirconium-silicon-based glass ceramics in Examples 1 to 5 under loads of 1kgf, 5kgf and 10kgf are 70μm, 70μm and 100μm, respectively;
[0038] Figure 3 This is a SEM image of the indentation trace of the zirconium-silicon-based glass ceramic 5MgO-65ZrO2-30SiO2 under a load of 30kgf in Example 2;
[0039] Figure 4The STEM-HAADF images and corresponding STEM-EDS elemental mappings of the zirconium-silicon-based glass-ceramics prepared in Examples 1 to 5 are shown in Figures 1 to 5; wherein (a) is the STEM-HAADF image of 5K2O-65ZrO2-30SiO2, (b) is the STEM-HAADF image of 5MgO-65ZrO2-30SiO2, (c) is the STEM-HAADF image of 5Al2O3-65ZrO2-30SiO2, (d) is the STEM-HAADF image of 5CeO2-65ZrO2-30SiO2, and (e) is the STEM-HAADF image of 5Ta2O5-6 STEM-HAADF image of 5ZrO2-30SiO2, (f) STEM-EDS elemental mapping of 5K2O-65ZrO2-30SiO2, (g) STEM-EDS elemental mapping of 5MgO-65ZrO2-30SiO2, (h) STEM-EDS elemental mapping of 5Al2O3-65ZrO2-30SiO2, (i) STEM-EDS elemental mapping of 5CeO2-65ZrO2-30SiO2, (j) STEM-EDS elemental mapping of 5Ta2O5-65ZrO2-30SiO2;
[0040] Figure 5 The STEM-HAADF images of zirconium-silicon-based glass ceramics prepared in Examples 1 to 3 with a scale of 100 nm and 50 nm are shown; wherein (a) and (b) are STEM-HAADF images of zirconium-silicon-based glass ceramics in Example 1 with a scale of 100 nm and 50 nm, respectively; (c) and (d) are STEM-HAADF images of zirconium-silicon-based glass ceramics in Example 2 with a scale of 100 nm and 50 nm, respectively; (e) and (f) are STEM-HAADF images of zirconium-silicon-based glass ceramics in Example 3 with a scale of 100 nm and 50 nm, respectively;
[0041] Figure 6 The STEM-HAADF images of zirconium-silicon-based glass ceramics prepared in Examples 4 and 5 with a scale of 100 nm and 50 nm, respectively; wherein (a) and (b) are STEM-HAADF images of zirconium-silicon-based glass ceramics in Example 4 with a scale of 100 nm and 50 nm, respectively, and (c) and (d) are STEM-HAADF images of zirconium-silicon-based glass ceramics in Example 5 with a scale of 100 nm and 50 nm, respectively;
[0042] Figure 7Characterization pictures of zirconium-silicon-based glass-ceramics in 1 to 5; wherein, (a) is the XRD pattern of the zirconium-silicon-based glass-ceramics in Examples 1 to 5, (b) is the grain size of the zirconium-silicon-based glass-ceramics in Examples 1 to 5, (c) is the low-magnification STEM-HAADF image of Example 25MgO-65ZrO2-30SiO2, (d) to (f) are high-magnification STEM-HAADF images of 5MgO-65ZrO2-30SiO2 in Example 2, and (g) is the ZrO2 particle distribution in Example 25MgO-65ZrO2-30SiO2;
[0043] Figure 8 1 is the XRD diagram of the zirconium-silicon-based glass-ceramics in Examples 1 to 10. DETAILED DESCRIPTION
[0044] The present invention provides a zirconium-silicon-based glass ceramic with ultra-high toughness and flexural strength, wherein the zirconium-silicon-based glass ceramic comprises the following components in molar percentage:
[0045] X 1~15%, ZrO225~70%, SiO225~70%;
[0046] Here, X is a metal oxide having a valence of +1 to +5.
[0047] In the present invention, X is preferably K2O, MgO, Al2O3, Y2O3, CeO2 or Ta2O5, more preferably K2O, MgO, Al2O3 or CeO2, and more preferably MgO or CeO2.
[0048] In the present invention, the molar percentage of X is preferably 1 to 15%, more preferably 4 to 10%, and even more preferably 5 to 8%.
[0049] In the present invention, the molar percentage of ZrO2 is preferably 25 to 70%, more preferably 41 to 64%, and even more preferably 52 to 63%.
[0050] In the present invention, the molar percentage of SiO2 is preferably 25 to 70%, more preferably 31 to 55%, and even more preferably 32 to 35%.
[0051] The present invention also provides a method for preparing zirconium-silicon-based glass ceramics with ultra-high toughness and flexural strength, comprising the following steps:
[0052] Mixing a precursor of X, a zirconium-based precursor, a silicon-based precursor and an alcohol solution to obtain a mixed solution;
[0053] adding an alkaline solution to the mixed solution for reaction, and aging the solution after the reaction is completed to obtain nanogel particles;
[0054] calcining the nanogel particles to obtain powder;
[0055] The powder is sintered to obtain zirconium-silicon-based glass ceramics.
[0056] In the present invention, the precursor of X is preferably potassium chloride, potassium nitrate, potassium isopropoxide, magnesium chloride, magnesium nitrate, aluminum chloride, aluminum nitrate, isopropoxide aluminum, yttrium chloride, yttrium nitrate, triisopropoxyyttrium, cerium chloride, cerium nitrate hexahydrate, tetraisopropoxycerium, tantalum nitrate, pentaisopropoxytantalum or tantalum chloride.
[0057] In the present invention, the zirconium-based precursor is preferably zirconium n-propoxide, zirconium dichloride or zirconium nitrate.
[0058] In the present invention, the silicon-based precursor is preferably tetraethyl orthosilicate, ethyl silicate, tetramethoxysilane or tetraisopropoxysilane.
[0059] In the present invention, the alcohol solution is preferably 1-propanol or anhydrous ethanol, more preferably 1-propanol.
[0060] In the present invention, the volume ratio of the zirconium-based precursor to the alcohol solution is preferably 0.5:1 to 1:10, more preferably 1:1 to 1:6, and more preferably 1:1.5 to 1:4.
[0061] In the present invention, the specific process of the mixing is:
[0062] First, the precursor of X is added to the alcohol solution, and stirred at 40° C. at a rotation speed of 550 rpm until the precursor of X is completely dissolved, and then the zirconium-based precursor and the silicon-based precursor are added and mixed.
[0063] In the present invention, the mixing temperature is preferably 20-50°C, more preferably 25-45°C, more preferably 30-40°C; the mixing time is preferably 0.5-2h, more preferably 0.75-1.5h, more preferably 1-1.25h; the mixing speed is preferably 500-1500rpm, more preferably 550-900rpm, more preferably 600-650rpm.
[0064] In the present invention, the alkaline solution is preferably an aqueous ammonia solution or a sodium hydroxide solution;
[0065] The concentration of the alkaline solution is preferably 0.1 to 2 mol / L, more preferably 0.5 to 1.3 mol / L, and more preferably 1 to 1.2 mol / L;
[0066] The volume ratio of the alcohol solution to the alkaline solution is preferably 1 to 8:1, more preferably 4 to 7:1, and even more preferably 5 to 6:1.
[0067] In the present invention, the process of adding the alkaline solution is as follows: adding the alkaline solution in batches under stirring conditions;
[0068] The stirring rate is preferably 500 to 1200 rpm, more preferably 600 to 1000 rpm, and more preferably 700 to 900 rpm;
[0069] The number of batches is preferably 17 to 50, more preferably 20 to 45, and even more preferably 25 to 35. The addition of the alkaline solution is to initiate hydrolysis, polymerization and precipitation of the sol.
[0070] In the present invention, the reaction temperature is preferably 20-50°C, more preferably 22-40°C, more preferably 25-30°C; the reaction time is preferably 8-15 min, more preferably 9-14 min, more preferably 10-12 min.
[0071] In the present invention, the aging temperature is preferably 20 to 90° C., more preferably 35 to 75° C., and more preferably 40 to 55° C.; the aging time is preferably 0.5 to 72 h, more preferably 1 to 48 h, and more preferably 1.5 to 36 h.
[0072] In the present invention, after the aging is completed, the method further comprises: drying the obtained product, and ball milling after the drying is completed;
[0073] The drying temperature is preferably 50 to 120° C., more preferably 65 to 110° C., and more preferably 70 to 90° C.; the drying time is preferably 1 to 48 hours, more preferably 5 to 36 hours, and more preferably 8 to 24 hours;
[0074] The ball milling time is preferably 30 to 150 min, more preferably 40 to 90 min, and even more preferably 55 to 60 min.
[0075] In the present invention, the calcination conditions are as follows: the initial temperature is preferably 20-30°C, more preferably 22-28°C, and more preferably 24-25°C; the final temperature is preferably 400-700°C, more preferably 450-630°C, and more preferably 520-600°C; the rate of increasing from the initial temperature to the final temperature is preferably 0.5-5°C / min, more preferably 1-4°C / min, and more preferably 1.5-3.5°C / min; the time of keeping at the final temperature is preferably 30-180min, more preferably 40-150min, and more preferably 60-120min. The purpose of calcination is to burn off the residual chemical substances.
[0076] In the present invention, the sintering method is preferably pressureless sintering, hot pressing sintering, hot isostatic pressing sintering or rapid sintering, and further preferably rapid sintering;
[0077] The rapid sintering is preferably spark plasma sintering or rapid hot pressing sintering, more preferably spark plasma sintering.
[0078] In the present invention, when the sintering method is spark plasma sintering, the sintering process is:
[0079] Under a pressure of 40 to 100 MPa, the temperature is raised from a first temperature of 350 to 400°C to a second temperature of 700 to 1000°C at a first heating rate of 80 to 150°C / min, and then raised to a third temperature of 1050 to 1250°C at a second heating rate of 20 to 50°C / min, and kept at that temperature for 3 to 7 minutes. After the end of the heating, the temperature is lowered to a fourth temperature of 700 to 800°C at a rate of 20 to 40°C / min;
[0080] The pressure is preferably 40 to 100 MPa, more preferably 50 to 85 MPa, and more preferably 60 to 75 MPa;
[0081] The first temperature is preferably 350 to 400°C, more preferably 366 to 380°C, and more preferably 370 to 375°C;
[0082] The second temperature is preferably 700 to 1000° C., more preferably 730 to 980° C., and more preferably 800 to 900° C.;
[0083] The first heating rate is preferably 80 to 150°C / min, more preferably 83 to 138°C / min, and more preferably 95 to 125°C / min;
[0084] The third temperature is preferably 1050-1250°C, more preferably 1130-1200°C, and more preferably 1145-1150°C;
[0085] The second heating rate is preferably 20 to 50°C / min, more preferably 25 to 43°C / min, and more preferably 30 to 38°C / min;
[0086] Keep warm for 3 to 7 minutes, more preferably 4 to 6 minutes, and more preferably 5 minutes;
[0087] Cooling at 20-40°C / min, more preferably 22-37°C / min, more preferably 25-30°C / min;
[0088] The fourth temperature is preferably 700-800° C., more preferably 720-780° C., and more preferably 730-750° C. Through pressure-assisted sintering, a ZrO2-SiO2 nano-glass ceramic in which spherical ZrO2 nano-grains with a grain size in the range of 10 nm to 100 nm are embedded in an amorphous SiO2 matrix is obtained. The tetragonal ZrO2 particles are embedded in the amorphous SiO2 matrix, and the doping elements are concentrated at the interface between the ZrO2 grains and the ZrO2 grains / glass matrix.
[0089] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0090] Example 1
[0091] A method for preparing zirconium-silicon-based glass ceramic 5K2O-65ZrO2-30SiO2 with ultra-high toughness and flexural strength comprises the following steps:
[0092] 2.53 g of potassium chloride was mixed with 250 mL of 1-propanol, and the mixture was stirred at 550 rpm at 40° C. until the potassium chloride was completely dissolved, and then 46 mL of tetraethyl orthosilicate and 200 mL of zirconium n-propoxide were added and mixed, and the mixture was stirred at 550 rpm at 30° C. for 0.5 h to obtain a mixed solution;
[0093] Add 50 mL of 0.1 mol / L ammonia solution (added in batches, 2 mL each time) to the mixed solution while stirring at 500 rpm, then stir at 25°C at 500 rpm for 10 min, age at 60°C for 72 h after stirring, dry the product at 80°C for 48 h, and ball mill for 45 min after drying to obtain gel particles;
[0094] The gel particles were heated from 25°C to 600°C at 1°C / min and calcined at 600°C for 1 h to obtain powder;
[0095] The powder was subjected to spark plasma sintering (SPS-825, Fuji Electronics Industry Co., Ltd., Japan); the sintering process was as follows: at a pressure of 60 MPa, it was heated from 400°C to 900°C at a rate of 125°C / min, and then further heated to 1150°C at a rate of 38°C / min, and kept warm for 5 minutes. After the end of the heat preservation, it was cooled to 800°C at a rate of 30°C / min to obtain zirconium-silicon-based glass ceramics 5K2O-65ZrO2-30SiO2, recorded as 5K-65Zr-30Si.
[0096] Example 2
[0097] A method for preparing zirconium-silicon-based glass ceramic 5MgO-65ZrO2-30SiO2 with ultra-high toughness and flexural strength comprises the following steps:
[0098] 3.24 g of magnesium chloride was mixed with 250 mL of 1-propanol, and the mixture was stirred at 550 rpm at 40° C. until potassium chloride was completely dissolved, and then 46 mL of tetraethyl orthosilicate and 200 mL of zirconium n-propoxide were added and mixed, and the mixture was stirred at 550 rpm at 30° C. for 0.5 h to obtain a mixed solution;
[0099] Add 50 mL of 0.1 mol / L ammonia solution (added in batches, 2 mL each time) to the mixed solution while stirring at 500 rpm, then stir at 25°C at 500 rpm for 10 min, age at 60°C for 72 h after stirring, dry the product at 80°C for 48 h, and ball mill for 45 min after drying to obtain gel particles;
[0100] The gel particles were heated from 25°C to 600°C at 1°C / min and calcined at 600°C for 1 h to obtain powder;
[0101] The powder was subjected to spark plasma sintering (SPS-825, Fuji Electronics Industry Co., Ltd., Japan); the sintering process was as follows: at a pressure of 60 MPa, it was heated from 400°C to 900°C at a rate of 125°C / min, and then further heated to 1150°C at a rate of 38°C / min, and kept warm for 5 minutes. After the end of the heat preservation, it was cooled to 800°C at a rate of 30°C / min to obtain zirconium-silicon-based glass ceramics 5MgO-65ZrO2-30SiO2, recorded as 5Mg-65Zr-30Si.
[0102] Example 3
[0103] A method for preparing zirconium-silicon-based glass ceramic 5Al2O3-65ZrO2-30SiO2 with ultra-high toughness and flexural strength comprises the following steps:
[0104] 6.94 g of aluminum isopropoxide was mixed with 250 mL of 1-propanol, and the mixture was stirred at 550 rpm at 40° C. until potassium chloride was completely dissolved, and then 46 mL of tetraethyl orthosilicate and 200 mL of zirconium n-propoxide were added and mixed, and the mixture was stirred at 550 rpm at 30° C. for 0.5 h to obtain a mixed solution;
[0105] Add 50 mL of 0.1 mol / L ammonia solution (added in batches, 2 mL each time) to the mixed solution while stirring at 500 rpm, then stir at 25°C at 500 rpm for 10 min, age at 60°C for 72 h after stirring, dry the product at 80°C for 48 h, and ball mill for 45 min after drying to obtain gel particles;
[0106] The gel particles were heated from 25°C to 600°C at 1°C / min and calcined at 600°C for 1 h to obtain powder;
[0107] The powder was subjected to spark plasma sintering (SPS-825, Fuji Electronics Industry Co., Ltd., Japan); the sintering process was as follows: at a pressure of 60 MPa, it was heated from 400°C to 900°C at a rate of 125°C / min, and then further heated to 1150°C at a rate of 38°C / min, and kept warm for 5 minutes. After the end of the heat preservation, it was cooled to 800°C at a rate of 30°C / min to obtain zirconium-silicon-based glass-ceramics 5Al2O3-65ZrO2-30SiO2, recorded as 5Al-65Zr-30Si.
[0108] Example 4
[0109] A method for preparing zirconium-silicon-based glass ceramic 5CeO2-65ZrO2-30SiO2 with ultra-high toughness and flexural strength comprises the following steps:
[0110] 14.76 g of cerium nitrate hexahydrate was mixed with 250 mL of 1-propanol, and the mixture was stirred at 550 rpm at 40° C. until potassium chloride was completely dissolved, and then 46 mL of tetraethyl orthosilicate and 200 mL of zirconium n-propoxide were added and mixed, and the mixture was stirred at 550 rpm at 30° C. for 0.5 h to obtain a mixed solution;
[0111] Add 50 mL of 0.1 mol / L ammonia solution (added in batches, 2 mL each time) to the mixed solution while stirring at 500 rpm, then stir at 25°C at 500 rpm for 10 min, age at 60°C for 72 h after stirring, dry the product at 80°C for 48 h, and ball mill for 45 min after drying to obtain gel particles;
[0112] The gel particles were heated from 25°C to 600°C at 1°C / min and calcined at 600°C for 1 h to obtain powder;
[0113] The powder was subjected to spark plasma sintering (SPS-825, Fuji Electronics Industry Co., Ltd., Japan); the sintering process was as follows: at a pressure of 60 MPa, it was heated from 400°C to 900°C at a rate of 125°C / min, and then further heated to 1150°C at a rate of 38°C / min, and kept warm for 5 minutes. After the end of the heat preservation, it was cooled to 800°C at a rate of 30°C / min to obtain zirconium-silicon-based glass ceramics 5CeO2-65ZrO2-30SiO2, recorded as 5Ce-65Zr-30Si.
[0114] Example 5
[0115] A method for preparing zirconium-silicon-based glass ceramic 5Ta2O5-65ZrO2-30SiO2 with ultra-high toughness and flexural strength comprises the following steps:
[0116] 12.18 g of tantalum chloride was mixed with 250 mL of 1-propanol, and the mixture was stirred at 550 rpm at 40° C. until potassium chloride was completely dissolved, and then 46 mL of tetraethyl orthosilicate and 200 mL of zirconium n-propoxide were added and mixed, and the mixture was stirred at 550 rpm at 30° C. for 0.5 h to obtain a mixed solution;
[0117] Add 50 mL of 0.1 mol / L ammonia solution (added in batches, 2 mL each time) to the mixed solution while stirring at 500 rpm, then stir at 25°C at 500 rpm for 10 min, age at 60°C for 72 h after stirring, dry the product at 80°C for 48 h, and ball mill for 45 min after drying to obtain gel particles;
[0118] The gel particles were heated from 25°C to 600°C at 1°C / min and calcined at 600°C for 1 h to obtain powder;
[0119] The powder was subjected to spark plasma sintering (SPS-825, Fuji Electronics Industry Co., Ltd., Japan); the sintering process was as follows: at a pressure of 60 MPa, it was heated from 400°C to 900°C at a rate of 125°C / min, and then further heated to 1150°C at a rate of 38°C / min, and kept warm for 5 minutes. After the end of the heat preservation, it was cooled to 800°C at a rate of 30°C / min to obtain zirconium-silicon-based glass ceramics 5Ta2O5-65ZrO2-30SiO2, recorded as 5Ta-65Zr-30Si.
[0120] Example 6
[0121] A method for preparing zirconium-silicon-based glass ceramics 5K2O-60ZrO2-35SiO2 and 10K2O-60ZrO2-30SiO2 with ultra-high toughness and bending strength is consistent with that in Example 1, except that:
[0122] When preparing 5K2O-60ZrO2-35SiO2 (5K-60Zr-35Si), the amount of potassium chloride used is 2.76 g, the amount of tetraethyl orthosilicate used is 58.1 mL, and the amount of zirconium n-propoxide used is 200 mL;
[0123] When preparing 10K2O-60ZrO2-30SiO2 (10K-60Zr-30Si), the amount of potassium chloride used is 5.52 g, the amount of tetraethyl orthosilicate used is 49.8 mL, and the amount of zirconium n-propoxide used is 200 mL.
[0124] Example 7
[0125] A method for preparing zirconium-silicon-based glass ceramics 5MgO-60ZrO2-35SiO2 and 10MgO-60ZrO2-30SiO2 with ultra-high toughness and bending strength is consistent with that in Example 1, except that:
[0126] When preparing 5MgO-60ZrO2-35SiO2 (5Mg-60Zr-35Si), the amount of magnesium chloride used is 3.52 g, the amount of tetraethyl orthosilicate used is 58.1 mL, and the amount of zirconium n-propoxide used is 200 mL;
[0127] When preparing 10MgO-60ZrO2-30SiO2 (10Mg-60Zr-30Si), the amount of magnesium chloride used is 7.05 g, the amount of tetraethyl orthosilicate used is 49.8 mL, and the amount of zirconium n-propoxide used is 200 mL.
[0128] Example 8
[0129] A method for preparing zirconium-silicon-based glass ceramics 5Al2O3-60ZrO2-35SiO2 and 10Al2O3-60ZrO2-30SiO2 with ultra-high toughness and bending strength is consistent with that in Example 1, except that:
[0130] When preparing 5Al2O3-60ZrO2-35SiO2 (5Al-60Zr-35Si), the amount of isopropoxide aluminum is 7.56 g, the amount of tetraethyl orthosilicate is 58.1 mL, and the amount of zirconium n-propoxide is 200 mL;
[0131] When preparing 10Al2O3-60ZrO2-30SiO2 (10Al-60Zr-30Si), the amount of isopropoxide aluminum used is 15.12 g, the amount of tetraethyl orthosilicate used is 49.8 mL, and the amount of zirconium n-propoxide used is 200 mL.
[0132] Example 9
[0133] A method for preparing zirconium-silicon-based glass ceramics 5CeO2-60ZrO2-35SiO2 and 10CeO2-60ZrO2-30SiO2 with ultra-high toughness and flexural strength is consistent with that in Example 1, except that:
[0134] When preparing 5CeO2-60ZrO2-35SiO2 (5Ce-60Zr-35Si), the amount of cerium nitrate hexahydrate used is 16.07 g, the amount of tetraethyl orthosilicate used is 58.1 mL, and the amount of zirconium n-propoxide used is 200 mL;
[0135] When preparing 10CeO2-60ZrO2-30SiO2 (10Ce-60Zr-30Si), the amount of cerium nitrate hexahydrate used is 32.13 g, the amount of tetraethyl orthosilicate used is 49.8 mL, and the amount of zirconium n-propoxide used is 200 mL.
[0136] Example 10
[0137] A method for preparing zirconium-silicon-based glass ceramics 5Ta2O5-60ZrO2-35SiO2 and 10Ta2O5-60ZrO2-30SiO2 with ultra-high toughness and bending strength is consistent with that in Example 1, except that:
[0138] When preparing 5Ta2O5-60ZrO2-35SiO2 (5Ta-60Zr-35Si), the amount of tantalum chloride used is 13.25 g, the amount of tetraethyl orthosilicate used is 58.1 mL, and the amount of zirconium n-propoxide used is 200 mL;
[0139] When preparing 10Ta2O5-60ZrO2-30SiO2 (10Ta-60Zr-30Si), the amount of tantalum chloride used is 26.51 g, the amount of tetraethyl orthosilicate used is 49.8 mL, and the amount of zirconium n-propoxide used is 200 mL.
[0140] Mechanical properties test:
[0141] The elastic modulus and nanohardness were measured using a nanoindentation tester (UltraNano Indenter, CSM Instruments, Switzerland), with a load of 8000μN applied at a rate of 8000μN / min, 20 indentations were performed on each sample, and three samples were selected for each group for testing; the fracture toughness was measured using a microindenter based on the indentation method, with a load of 8000μN applied at a rate of 8000μN / min, 5 indentations were performed on each sample at different positions, and the microhardness was measured. The indentation diagonal (α) and the crack length (l) from the diagonal edge were observed using a microindentation tester and SEM, respectively. The fracture toughness was calculated using the NiiharaK method for Palmqvist cracks.
[0142] The piston-three-ball test was performed on a polished sample supported by three balls distributed on a circle with a radius of 3.445 mm. A universal testing machine (Autograph AGS-H; Shimadzu, Japan) was used. The biaxial bending strength was calculated according to ISO 6872 standard.
[0143] The toughness and bending strength of the zirconium-silicon-based glass-ceramics 5K2O-65ZrO2-30SiO2, 5MgO-65ZrO2-30SiO2, 5Al2O3-65ZrO2-30SiO2, 5CeO2-65ZrO2-30SiO2, and 5Ta2O5-65ZrO2-30SiO2 prepared in Examples 1 to 5 are as follows: Figure 1 As shown in (a). Figure 1 As shown in (a), 5MgO-65ZrO2-30SiO2 shows significantly higher toughness, which is 12.39±1.34MPa·m 1 / 2 , followed by 5CeO2-65ZrO2-30SiO2 (11.52±1.63MPa·m 1 / 2 ), 5Al2O3-65ZrO2-30SiO2 (8.19±1.49MPa·m 1 / 2 ), 5Ta2O5-65ZrO2-30SiO2 (6.94±0.86MPa·m 1 / 2 ) and 5K2O-65ZrO2-30SiO2 (5.54±0.35MPa·m 1 / 2 ); 5K2O-65ZrO2-30SiO2 showed the highest flexural strength of 910±52MPa, followed by 5CeO2-65ZrO2-30SiO2, 5Ta2O5-65ZrO2-30SiO2, 5MgO-65ZrO2-30SiO2 and 5Al2O3-65ZrO2-30SiO2.
[0144] The nanohardness and elastic modulus of the zirconium-silicon-based glass ceramics 5K2O-65ZrO2-30SiO2, 5MgO-65ZrO2-30SiO2, 5Al2O3-65ZrO2-30SiO2, 5CeO2-65ZrO2-30SiO2, and 5Ta2O5-65ZrO2-30SiO2 prepared in Examples 1 to 5 are as follows: Figure 1 As shown in (b). Figure 1As can be seen from (b), 5MgO-65ZrO2-30SiO2 shows the highest nanohardness and elastic modulus values, which are 11.86±0.89 GPa and 203.55±13.98 GPa, respectively; in comparison, 5CeO2-65ZrO2-30SiO2 shows the lowest hardness, which is 9.88±0.65 GPa, while 5K2O-65ZrO2-30SiO2 has the lowest elastic modulus, which is 127.99±7.69 GPa.
[0145] Figure 1 (c) is the bending strength and toughness diagram of lithium silicate glass ceramics. Figure 1 The illustration in (c) is a comparison of the indentation traces of lithium silicate glass ceramics and zirconium silicon-based glass ceramics 5MgO-65ZrO2-30SiO2 prepared in Example 2 under a load of 1 kgf. Figure 1 As can be seen in (c), the classic radial cracks starting from the corners of the Vickers indentation are clearly visible. The lithium silicate glass ceramics show significantly longer cracks, while the 5MgO-65ZrO2-30SiO2 sample has no visible cracks.
[0146] Figure 1 (d) is a SEM image of the fracture surface of the zirconium-silicon-based glass ceramic 5MgO-65ZrO2-30SiO2 prepared in Example 2. Figure 1 The inset in (d) is a higher magnification SEM image of the fracture surface of 5MgO-65ZrO2-30SiO2. Figure 1 As can be seen in (d), nanoscale particles and holes can be seen on the fracture surface of 5MgO-65ZrO2-30SiO2, indicating that the fracture occurred along the interface, showing a shell-like fracture behavior.
[0147] Figure 1 (e) shows the appearance of lithium silicate glass ceramics and 5MgO-65ZrO2-30SiO2 after a load of 30kgf is applied. Figure 1 As can be seen in (e), the lithium silicate glass ceramic broke during the test, while the 5Mg-65Zr-30Si remained intact.
[0148] Figure 1 (f) is a representative SEM image of the indentation crack end of the zirconium-silicon-based glass-ceramic 5MgO-65ZrO2-30SiO2 in Example 2, revealing intergranular cracks that progress along the ZrO2 grain boundaries.
[0149] Figure 1(g) is a representative SEM image of the indentation crack end of 5MgO-65ZrO2-30SiO2 after hydrofluoric acid (HF) acid etching (10% HF solution etching for 90s), and crack deflection, bridging and branching were observed, revealing crack deflection and crack bridging.
[0150] The above observations indicate that micro and macro cracks propagate along interfaces rather than within the glass matrix and grains.
[0151] Material Characterization:
[0152] The phase composition was confirmed by X-ray diffraction (XRD), using a Bruker D8 double diffractometer in the 2θ range of 10 to 80° with a scanning speed of 2° / min. The grain size of ZrO2 nanocrystals was calculated using the Scherrer equation, and the (101) crystal plane of tetragonal ZrO2 was selected for calculation. The morphology of the glass-ceramics was analyzed by scanning electron microscopy (SEM, Merlin, Zeiss, Germany). In order to resolve the ZrO2 grains, the samples were etched in an HF bath to remove the SiO2 phase and then observed. The microstructure and element distribution were further examined using transmission electron microscopy (TEM, FEI Company, the Netherlands) and electron energy loss spectroscopy (EELS) and GIF quantum filter (Gatan, Inc., Pleasanton, California, USA).
[0153] Figure 2 The SEM images of the indentation marks of lithium silicate glass ceramics and zirconium-silicon-based glass ceramics 5K2O-65ZrO2-30SiO2, 5MgO-65ZrO2-30SiO2, 5Al2O3-65ZrO2-30SiO2, 5CeO2-65ZrO2-30SiO2, 5Ta2O5-65ZrO2-30SiO2 prepared in Examples 1 to 5 under loads of 1kgf, 5kgf and 10kgf, wherein the scales in the SEM images of the indentation marks of lithium silicate glass ceramics under loads of 1kgf, 5kgf and 10kgf are 70μm, 100μm and 100μm, respectively; the scales in the SEM images of the indentation marks of zirconium-silicon-based glass ceramics in Examples 1 to 5 under loads of 1kgf, 5kgf and 10kgf are 70μm, 70μm and 100μm, respectively. Figure 2 It can be seen that the cracks of the magnesium-doped sample 5MgO-65ZrO2-30SiO2 are significantly shorter than those of the potassium-doped sample 5K2O-65ZrO2-30SiO2. As the load increases, the crack length increases.
[0154] Figure 3 This is a SEM image of the indentation trace of the zirconium-silicon-based glass ceramic 5MgO-65ZrO2-30SiO2 under a load of 30kgf in Example 2. Figure 3It can be seen that even under a pressure of 30 kgf, the length of the crack is less than 100 microns. In comparison, for lithium silicate glass ceramics, the samples are broken under a pressure of 30 kgf.
[0155] The mechanical properties of the zirconium-silicon-based glass-ceramics in Examples 1 to 10 are shown in Table 1.
[0156] Table 1 Mechanical properties of zirconium-silicon-based glass ceramics in Examples 1 to 10
[0157]
[0158] Figure 4 STEM-HAADF images and corresponding STEM-EDS elemental mappings of zirconium-silicon-based glass-ceramics 5K2O-65ZrO2-30SiO2, 5MgO-65ZrO2-30SiO2, 5Al2O3-65ZrO2-30SiO2, 5CeO2-65ZrO2-30SiO2, and 5Ta2O5-65ZrO2-30SiO2 prepared in Examples 1 to 5.
[0159] Figure 5 , 6 These are STEM-HAADF images with scales of 100nm and 50nm of zirconium-silicon-based glass-ceramics 5K2O-65ZrO2-30SiO2, 5MgO-65ZrO2-30SiO2, 5Al2O3-65ZrO2-30SiO2, 5CeO2-65ZrO2-30SiO2, and 5Ta2O5-65ZrO2-30SiO2 prepared in Examples 1 to 5.
[0160] Depend on Figure 4 , 5 , 6, two different phases with different contrasts can be clearly observed, where the elliptical crystalline phase is uniformly distributed in the darker matrix. In STEM-HAADF imaging mode, the ring detector collects scattered electrons, showing that the brightness of the micrograph depends on the atomic number Z. Therefore, the brighter elliptical shape corresponds to the ZrO2 nanocrystals. The STEM-EDS results also confirmed that the brighter ZrO2 nanocrystalline phase is uniformly embedded in the darker SiO2 amorphous phase. The doping elements show different distributions, with Mg 2+ 、Al 3+ and Ce 4+ A core-shell structure was observed in the elemental mapping, indicating that the doping elements were strongly concentrated at the ZrO2 grain boundaries and ZrO2-SiO2 interfaces. + and Ta 5+ It is mainly dissolved in ZrO2 grains and slightly aggregated at the interface.
[0161] The XRD patterns of the zirconium-silicon-based glass ceramics 5K2O-65ZrO2-30SiO2, 5MgO-65ZrO2-30SiO2, 5Al2O3-65ZrO2-30SiO2, 5CeO2-65ZrO2-30SiO2, and 5Ta2O5-65ZrO2-30SiO2 prepared in Examples 1 to 5 are as follows: Figure 7 As shown in (a).
[0162] The XRD patterns of the zirconium-silicon-based glass ceramics prepared in Examples 1 to 10 are as follows: Figure 8 shown.
[0163] Depend on Figure 7 (a) and Figure 8 It can be seen that two crystal phases are mainly identified from the diffraction patterns of all samples, namely tetragonal ZrO2 (t-ZrO2) and monoclinic ZrO2 (m-ZrO2). The monoclinic phase occurs due to the phase transition of the tetragonal phase during cooling. Aliovalent doping elements with larger or smaller radii may help to improve the stability of t-ZrO2 to monoclinic distortion because the relaxed oxygen atoms show strong attraction to the oxygen vacancies induced by the doping elements; this process in turn leads to the distortion of the structure, thereby reducing the tetragonality of the crystal.
[0164] The grain sizes of the zirconium-silicon-based glass ceramics 5K2O-65ZrO2-30SiO2, 5MgO-65ZrO2-30SiO2, 5Al2O3-65ZrO2-30SiO2, 5CeO2-65ZrO2-30SiO2, and 5Ta2O5-65ZrO2-30SiO2 obtained in Examples 1 to 5 are shown in FIG. Figure 7 As shown in (b), since the doping elements are segregated at the interface, it can control the grain growth behavior during sintering due to the difficulty of nucleation (impurity drag force). Figure 7 Figure (b) illustrates the grain size of glass ceramics (GC) doped with different elements. K2O doped ZrO2-SiO2 GC shows the smallest grain size of 25.8 ± 8.1 nm. With increasing valence, the grain size increases and Ta2O5 doping reaches the highest value of 48.6 ± 17.7 nm for ZrO2-SiO2 GC.
[0165] Figure 7 (c) is a low magnification STEM-HAADF image of 5MgO-65ZrO2-30SiO2 in Example 2. Figure 7 As can be seen in (c), the ZrO2 particles are mainly elliptical in shape.
[0166] according to Figure 7 (c) The ZrO2 particle distribution in 5MgO-65ZrO2-30SiO2 is calculated. The result is as follows: Figure 7 As shown in (g). Figure 7 As can be seen in (g), the ZrO2 particle size follows a Gaussian distribution.
[0167] Figure 7 (d) to (f) are high magnification STEM-HAADF images of 5MgO-65ZrO2-30SiO2 in Example 2. Figure 7 (d), (e) and (f) show the triple connection between three grains and the grain boundary between grains, respectively, and the thickness of the grain boundary is less than 1nm.
[0168] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A zirconium-silicon-based glass ceramic with ultra-high toughness and flexural strength, characterized in that: The zirconium-silicon-based glass ceramics include the following components in molar percentage: X 1~15%, ZrO225~70%, SiO225~70%; Here, X is a metal oxide having a valence of +1 to +5.
2. The zirconium-silicon-based glass-ceramic with ultra-high toughness and flexural strength according to claim 1, characterized in that: The X is K2O, MgO, Al2O3, Y2O3, CeO2 or Ta2O5.
3. The method for preparing the zirconium-silicon-based glass ceramics with ultra-high toughness and flexural strength according to claim 1 or 2, characterized in that: The following steps are involved: Mixing a precursor of X, a zirconium-based precursor, a silicon-based precursor and an alcohol solution to obtain a mixed solution; adding an alkaline solution to the mixed solution for reaction, and aging the solution after the reaction is completed to obtain nanogel particles; calcining the nanogel particles to obtain powder; The powder is sintered to obtain zirconium-silicon-based glass ceramics.
4. The method for preparing zirconium-silicon-based glass ceramics with ultra-high toughness and flexural strength according to claim 2, characterized in that: The precursor of X is potassium chloride, potassium nitrate, potassium isopropoxide, magnesium chloride, magnesium nitrate, aluminum chloride, aluminum nitrate, isopropoxide aluminum, yttrium chloride, yttrium nitrate, triisopropoxide yttrium, cerium chloride, cerium nitrate hexahydrate, tetraisopropoxide cerium, tantalum nitrate, pentaisopropoxide tantalum or tantalum chloride; The zirconium-based precursor is zirconium n-propoxide, zirconium dichloride or zirconium nitrate; The silicon-based precursor is tetraethyl orthosilicate, ethyl silicate, tetramethoxysilane or tetraisopropoxysilane; The alcohol solution is 1-propanol or anhydrous ethanol.
5. The method for preparing zirconium-silicon-based glass ceramics with ultra-high toughness and flexural strength according to claim 4, characterized in that: The volume ratio of the silicon-based precursor to the alcohol solution is 0.5:1 to 1:
10.
6. The method for preparing zirconium-silicon-based glass ceramics with ultra-high toughness and flexural strength according to claim 5, characterized in that: The mixing temperature is 20-50° C., the mixing time is 0.5-2 h, and the mixing speed is 500-1500 rpm.
7. The method for preparing zirconium-silicon-based glass ceramics with ultra-high toughness and flexural strength according to claim 5 or 6, characterized in that: The alkaline solution is an aqueous ammonia solution or a sodium hydroxide solution; The concentration of the alkaline solution is 0.1-2 mol / L; The volume ratio of the alcohol solution to the alkaline solution is 1 to 8:
1.
8. The method for preparing zirconium-silicon-based glass ceramics with ultra-high toughness and flexural strength according to claim 7, characterized in that: The aging temperature is 20-90° C., and the aging time is 0.5-72 h.
9. The method for preparing zirconium-silicon-based glass ceramics with ultra-high toughness and flexural strength according to claim 8, characterized in that: The calcination conditions are as follows: the initial temperature is 20-30°C, the final temperature is 400-700°C, the rate of increasing from the initial temperature to the final temperature is 0.5-5°C / min, and the time of keeping at the final temperature is 30-180min.
10. The method for preparing zirconium-silicon-based glass ceramics with ultra-high toughness and flexural strength according to claim 9, characterized in that: The sintering method is pressureless sintering, hot pressing sintering, hot isostatic pressing sintering or rapid sintering; The rapid sintering is spark plasma sintering or rapid hot pressing sintering.
Citation Information
Cited By
Zirconium-silicon-based glass ceramic having ultra-high toughness and bending strength, and preparation method therefor
WO2026067421A1
